Subacute combined spinal cord degeneration and pancytopenia secondary to severe vitamin B12 deficiency - Cabrerizo-García, José Luis; Sebastián-Royo, Mariano; Montes, Nerea; Zalba-Etayo, Begoña (São Paulo Medical Journal, 2012)
CONTEXT: Decreased vitamin B12 concentration does not usually result in clinical or hematological abnormalities. Subacute combined spinal cord degeneration and pancytopenia are two serious and rarely displayed consequences that appear in severe deficits. CASE REPORT: We present the case of a patient with subacute combined spinal cord degeneration and pancytopenia secondary to severe and sustained vitamin B12 deficiency. Such cases are rare nowadays and have potentially fatal consequences. CONCLUSIONS: Vitamin B12 deficiency should be taken into consideration in the differential diagnosis in cases of blood disorders or severe neurological symptoms. Early diagnosis and treatment can avoid irreversible consequences.